PENGARUH MEDIA PEMBELAJARAN WAYANG MODIFIKASI TERHADAP PENGETAHUAN PENDIDIKAN SEKS ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Tania Ayu Kencana Putri; Ria Novianti; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on observation in the field it can be seen that the sex education knowledge of children 5-6 years old has not developed optimally. So need to use a wayang modification learning media on the sex education knowledge. This research was conducted at TK Negeri Pembina 1 Pekanbaru. This research use experiment method with one group pre-test post-test design with 15 total samples of children. Technique of collecting data in this research use test. Technique of data analysis use t-test with SPSS Windows Ver. 19. The result of data analysis is t arithmetic = 15,120 bigger than t table = 2,145 with sig. 0,00 < 0,05. The conclusion in this research is there are differences in sex education knowledge before and after using wayang modification learning media. The effect given by the modification wayang learning media based on N Gain formula is 68,23%.Keywords : Sex Education Knowledge, Wayang Modification Learning Media